Using photographic images as an alternative method to enhance learning process in pre-school level / Farihan Zaharia...[et.al] - Zaharia, Farihan; Alias, Aidah (2016)
In this research, researcher chooses a pre-school level for the subject matter of this study. Researcher interested to study about the effectiveness using image photography to enhance learning process in pre-school level. The objectives of pre-school or kindergarten is to nurture the pupils' learning potential in the aspect of growth, mastering the basic skills and cultivating positive traits. This is as a preparation of entering the next level that is primary school. Language development occurs progressively and a child's symbolic way of thinking starts around this period of which is also known as the pre-operational period. Within this phase, children is said to be able to develop logical thinking albeit one-way and that this ability is restricted due to their inability to think the other way around. For that reason, researchers are highly interested in investigating the effectiveness of photographical image usage when it is applied in pupils' learning process in pre-school level.